Recontextualizing The Essence Of Human Dignity Through Fazlur Rahmans Double Movement Hermeneutics Of Qs. Al-Isra (17): 70 - Ahmad Isnaeni; Anjela Kharomah; Ikhlas Sabili Huda; Livia Rossi Alfareza; Maulana Halim Hafiz (Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2026)
ok